Assessment of Visual Skills Impact on Motor Performance of Soccer Players in Ethiopian Youth Sport Academy - Biruk Sorate (Selcuk University, 2020)
The purpose of the study was to assess the impact of visual skills on motor performance of soccer players in Ethiopian youth sport academy. Cross-sectional study design was employed and 62 subjects (28 male and 34 female) were participated using purposive and availability sampling methods. The primary sources of data such as demographic characteristics, the visual skill tests and motor performance were measured. The results presented as mean ± SD, and Frequency proportions were used to show the visual skill status. A Multivariate Roy's Largest Root Tests was used to examine the impacts of visual skills on motor performance and one way ANOVA was used to show the difference of visual skills and motor performance in playing positions. Whereas, Pearson product moment correlation coefficient was used to test the relationship between visual skills and motor performances. SPSS version 20 software was used to analyze the data and the significance values set at p-value 0.05 levels to all statistical analysis. The result indicates that 26(42%) of players had no color blindness, 32(52%) had some degree of color blindness and 4(6%) of them had weak color blindness status. There was significant differences of eye foot coordination test between playing position in score of F = 3.669, P lt; 0.05 (0.017). Color blindness has a positive significant correlation with motor performance in reaction time (r = 0.343, r2 = 0.1176, P lt; 0.01). Based on the result the researcher concluded that there was significant difference in eye foot coordination between playing positions. Color blindness significantly and positively correlated with motor performance to reaction time. And also visual acuity significantly and positively correlated with motor performance to eye hand coordination.